2021
DOI: 10.3390/biom12010017
|View full text |Cite
|
Sign up to set email alerts
|

Do Epstein–Barr Virus Mutations and Natural Genome Sequence Variations Contribute to Disease?

Abstract: Most of the world’s population is infected by the Epstein–Barr virus (EBV), but the incidence of the diseases associated with EBV infection differs greatly in different parts of the world. Many factors may determine those differences, but variation in the virus genome is likely to be a contributing factor for some of the diseases. Here, we describe the main forms of EBV genome sequence variation, and the mechanisms by which variations in the virus genome are likely to contribute to disease. EBV genome deletion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 64 publications
(95 reference statements)
0
10
0
Order By: Relevance
“…The 172-nt sequence of EBER2 is generally well-conserved among EBV strains recovered from B cell lymphomas and lymphoma-derived B cell lines. However, it was reported recently that some EBV strains, including strain M81, which displays differential association with nasopharyngeal carcinoma ( 14 , 15 ), carry EBER2 single nucleotide polymorphisms (SNPs) that may contribute to the virus life cycle ( 16 19 ). Included among the M81 EBER2 SNPs are nucleotides at positions 44, 46, 57, 61, 93, 168, and 170 that are present in M81 and many EBV strains from China but differ from the nucleotides that are conserved among most EBV strains from other parts of the world ( 14 , 15 ), including the B95-8 EBER2 expressed by the ΔT4.E2.b virus.…”
Section: Observationmentioning
confidence: 99%
“…The 172-nt sequence of EBER2 is generally well-conserved among EBV strains recovered from B cell lymphomas and lymphoma-derived B cell lines. However, it was reported recently that some EBV strains, including strain M81, which displays differential association with nasopharyngeal carcinoma ( 14 , 15 ), carry EBER2 single nucleotide polymorphisms (SNPs) that may contribute to the virus life cycle ( 16 19 ). Included among the M81 EBER2 SNPs are nucleotides at positions 44, 46, 57, 61, 93, 168, and 170 that are present in M81 and many EBV strains from China but differ from the nucleotides that are conserved among most EBV strains from other parts of the world ( 14 , 15 ), including the B95-8 EBER2 expressed by the ΔT4.E2.b virus.…”
Section: Observationmentioning
confidence: 99%
“…The development of high‐throughput sequencing technologies has enabled sequencing of EBV genomes derived from a wide variety of clinical samples. In addition, the sequences of EBV genes/genomes vary geographically, and several geographically specific high‐risk EBV subtypes for NPC or other tumors have been identified 11–16 . Recently, studies from NPC‐endemic China have shown that two single‐nucleotide polymorphisms (SNPs) of BALF2, T162476C and C163364T, are associated with risk of NPC 16 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the sequences of EBV genes/genomes vary geographically, and several geographically specific high-risk EBV subtypes for NPC or other tumors have been identified. [11][12][13][14][15][16] Recently, studies from NPCendemic China have shown that two single-nucleotide polymorphisms (SNPs) of BALF2, T162476C and C163364T, are associated with risk of NPC. 16 EBV was the first human virus shown to encode microRNAs (miRNAs).…”
Section: Introductionmentioning
confidence: 99%
“…However almost nothing is known about differences between T1 and T2 EBV infection in epithelial cells. T1 EBV infection is much more common than T2 EBV infection in western countries [30] and most previous studies in the EBV field have been performed using T1 EBV strains. T2 EBV infection has been reported to be present in up to 50% of the population in sub-Saharan Africa and New Guinea [15][16][17][18][19][20][21][22], and humans can be simultaneously infected with both types [21,22].…”
Section: Introductionmentioning
confidence: 99%